An alternative modal representation of a symmetrical nontransposed three-phase transmission line - Kurokawa, Sergio; Daltin, Rodrigo S.; Prado, Afonso. J.; Pissolato, Jose (Institute of Electrical and Electronics Engineers (IEEE), 2007)
The objective of this letter is to propose an alternative modal representation of a nontransposed three-phase transmission line with a vertical symmetry plane by using two transformation matrices. Initially, Clarke's matrix is used to separate the line into components a, 0, and zero. Because a and zero components are not exact modes, they can be considered as being a two-phase line that will be decomposed in its exact modes by using a 2 x 2 modal transformation matrix. This letter will describe the characteristics of the two-phase line before mentioned. This modal representation is applied to decouple a nontransposed three-phase transmission line with a vertical symmetry plane whose nominal voltage is 440 kV.
Keywords: frequency domain analysis; multimode transmission line; transmission line matrix methods; transmission line theory